The dark tree : jazz and the community arts in Los Angeles - Isoardi, Steven Louis, 1949- (Duke University Press, 2023)
"In the early 1960s, pianist Horace Tapscott gave up a successful career in Lionel Hampton's band and returned to his home in Los Angeles to found the Pan Afrikan Peoples Arkestra, a community arts group that focused on providing community-oriented jazz and jazz training. Over the course of almost forty years, the Arkestra, together with the related Union of God's Musicians and Artists Ascension Foundation, were at the forefront of the vital community-based arts movements in black Los Angeles. Some three hundred artists-musicians, vocalists, poets, playwrights, painters, sculptors, and graphic artists-passed through these organizations, many ultimately remaining within the community and others moving on to achieve international fame. In The Dark Tree, Steven L. Isoardi draws on one hundred in-depth interviews with the Arkestra's participants to tell the history of the important and largely overlooked community arts movement of African American Los Angeles. This revised and updated edition brings the story of the Arkestra up to date, as its ethos and aesthetic remain vital forces in jazz and popular music to this day"--